(untitled) (World Bulletin of Public Health, 2023)
The article provides data on the definition and rationale for the inclusion of immunomodulin in a complex of therapeutic measures for sick young children with acute obstructive bronchitis and bronchiolitis . The effectiveness of the drug immunomodulin was assessed by the period (days) of disappearance of symptoms of respiratory failure and intoxication in children during the period of treatment.